Gaya Hidup, Sosial Media,Teman Sebaya:Terhadap Perilaku Konsumtif Belanja Online Ditiktok Mahasiswa UNM - Sahabuddin, Romansyah; Arimayanti, Angnis; Mutmainna, Rizka; Nurfuraya; Nuraisyah (Yayasan Literasi Sains Indonesia, 2023)
This research discusses the role of social media lifestyle and peers in consumer behavior when shopping for online fashion products on the TikTok platform. With the aim of knowing the impact of lifestyle on consumptive behavior, the impact of social media on consumptive behavior, the impact of peers on consumptive behavior. The variables used are Lifestyle (X1), social media (X2) and peers (X3) as independent variables and Consumptive Behavior (Y) as the dependent variable. The assessment method applied is quantitative methodology. The information gathering strategy implemented was by providing questionnaires. This research consisted of Makassar State University (UNM) students with a sample of 80 respondents. These data were tested using structural equation modeling (SEM) techniques and using the SmartPLS (Partial Least Squares) software analysis tool. Lifestyle (X1) The results of this study state ththere is a significant influence on Consumptive Behavior (Y). Social media (X2) has a significant effect on consumer behavior (Y) and peers (X3) have no effect on consumer behavior (Y).